ADHM polytopes - James P. Allen; Paul Sutcliffe (Journal of High Energy Physics, 2013)
Inflammatory bowel disease (IBD) was a chronic idiopathic disorder affecting the ileum, rectum, and colon, characterized by substantial disruptions in the gut microbiota that ultimately led to dysbiosis. Such microbial imbalance compromised intestinal barrier integrity, facilitating the translocation of enterogenous urinary toxins and opportunistic pathogens into the bloodstream. This process subsequently activated intestinal mucosal immunity, triggers systemic microinflammatory responses, and exacerbated kidney injury. Herein, we reported a biocompatible, carrier-free nanomachine system based on tungsten trioxide (WO 3 ) for the active delivery of WO 3 to protect both the intestines and kidneys by preserving intestinal homeostasis via the gut-kidney axis in vivo. Platinum (Pt) nanoparticles were asymmetrically deposited onto the surface of WO 3 to enable controlled O 2 release in response to the in vivo microenvironment. The locally generated O 2 not only acted synergistically with WO 3 to ameliorate intestinal and renal damage but also served as a propellant to drive nanomachine motion. Upon accumulation in intestinal tissues, the nanomachines exhibited reactive oxygen species (ROS)-responsive autonomous movement, which enhanced WO 3 diffusion and promoted therapeutic efficacy. This targeted motion facilitated intestinal injury repair, restored intestinal homeostasis, and consequently improved renal function. Overall, this rationally designed nanomachine system represented a promising platform for the combined protection of intestinal and renal health through modulation of intestinal homeostasis.